Psychological counseling needs among middle and high school students with separated/divorced parents in Hue city - Tran, Binh Thang; Ho, Uyen Phuong; Dinh, Thi Lieu; Pham, Thi Thu Ha; Chau, Nguyen Dan; Nguyen, Ngo Bao Khuyen; Luong, Thi Thu Tham; Tran, Thi Tra My; Vo, Nu Hong Duc; Nguyen, Thanh Gia; Nguyen, Van Thong; Nguyen, Minh Tam; et al. (Tạp chí Y Dược Huế, 2023)
Background: Adolescents who live in incomplete families may be vulnerable to various psychological effects, ranging from mild to complex. This study aims to examine the need for psychological counseling among high school students whose parents are separated/divorced, and to identify factors associated with this need. Methods: A cross-sectional descriptive study was conducted on 309 high school students with separated/separated/divorced parents in Hue City. Results: The percentage of high school students with separated/divorced parents who need psychological counseling accounted for 40.5%. The need for psychological consultation about life skills and future orientation accounted for 54.4%, appearance and physicality accounted for 37.9%, family relationships accounted for 33.0% and problems with reproductive health and heterosexual friendship accounted for 31.4%. Factors related to the need for psychological counseling include the time of parents’ divorce, close friendship relationship, problems with friends, behavioral problems, violence, family quality and school quality, with a significance level of p < 0.05. Conclusion: High school students with separated/divorced parents need psychological counseling, so it is necessary to combine family and school to create a healthy environment for children.